Potensi Senyawa Metabolit Sekunder Infusum Daun Durian (Durio zibethinus) Terhadap Kelulushidupan Ikan Nila (Oreochromis niloticus) Pada Transportasi Ikan Hidup Sistem Kering [ The Secondary Metabolites Potential Of Infusum Durian's (Durio zibethinus) Leaves Effect To Survival Rate Of Nila (Oreochromis niloticus) On The Livefish Dry Transport System] - Endang Dewi Masithah; Muhammad Sholihul Abid; Prayogo Prayogo (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Nila (Oreochromis niloticus) is one of the leading commodity and each year will always be increased in both local and export markets. It's in line and will continue to grow due to the tendency of shifting market demand for commodities is of the dead form of fish (frozen) or other processed into a form of life, especially for the needs of breeders on commodity stocks. One of the latest post-harvest technologies that can be applied in the handling of live fish is a fish transport system in the dry media without use of water as a medium of transport with the use of anesthesia using plants that naturally contain active compounds that have the potential as a anesthesia drugs. This study aimed to determine the length of time different fish living on the transportation system with particular concentration infusum dried leaves of durian (Durio zibethinus) effect on the survival rate of nila (O. niloticus). Methods of this study is an experiment with three replications with different concentration intervals. It consisted of a preliminary study to determine the potential infusum durian leaves as anesthesia and primary research material as a form of media applications on the system dry. This study was conducted at the Laboratory of the Faculty of Fisheries and Marine Airlangga University. The results showed that the effective concentration of durian leaves infusum used to transport test was 4100 ppm with an average induction time is 40 minutes and recovery time is 48 minutes. Durian leaves infusum use in nila with 4100 ppm concentration able to achieve the level of survival and long transportation times in a row 100%, 0 h, 88.89%; 2 h, 22.22%; 4 h, 0%; 6 h, and 0%, 8 h on media packaging live fish without water.